Undernutrition and associated factors among school-age children in Wolaita Zone, South Ethiopia: a comparative cross-sectional study - Meskele, Dereje Kutafo; Abiso, Temesgen Lera; Belete, Tinsae Bekele; Koyira, Mengistu Meskele; Dake, Samson Kastro (Frontiers in Nutrition, 2024)
Background Nutritional deficiencies in school-age children are a public health concern, especially in resource-limited countries. A school feeding program involves the provision of food on-site or taken home to reduce hunger. It is implemented in several developing nations; however, little is known about the association of school feeding programs with the nutritional status of school-age children in the study area. Objectives The study aimed to determine the magnitudes and associated factors of undernutrition among school-age children with school feeding programs (SFPs) and non-school feeding programs (N-SFPs) in Kindo Didaye woreda, South Ethiopia. Methods A school-based comparative cross-sectional study was conducted in Kindo Didaye district from May to June 2023. A total of 612 participants were included in the study. The data were collected from each selected student's parents by using a structured interviewer-administered questionnaire. The weight and height of the children were measured, and a household dietary diversity assessment was conducted. The data were analyzed using SPSS version 25. A binary logistic regression analysis was carried out. A p-value of <0.05 and 95% confidence interval (CI) were used to establish a statistically significant association. Results The magnitude of undernutrition among the school-age children was 38.9%: 43.3% in the children from the SFP schools and 34.5% in the children from the N-SFP schools. Stunting was 24.1% among the children in the schools with SFPs and 16% among the children in the N-SFP schools, whereas thinness was 33.8% among the children in the SFP schools and 25.6% among the children in the N-SFP schools. The children who were in the older age group [adjusted odds ratio (AOR) = 4.4, 95%CI; 2.22–8.85], consumed less than three meals per day at home (AOR = 6.03; 95%CI 3.9–9.3), and did not eat breakfast at all before going to school (AOR = 3.5; 95%CI 1.15–10.76) were more likely to become undernourished. The children whose fathers received secondary and above education (AOR = 0.52; 95% CI (0.27–0.971) had lower odds of becoming underweight. Conclusion The magnitude of undernutrition was high in the current study. Existing interventions that work to improve the nutritional status of school-age children should be strengthened. Children should consume any type of food as breakfast at home before going to school regardless of the presence of school feeding programs and at least three times a day.